In vitro and in vivo targeting properties of iodine-123- or iodine-131-labeled monoclonal antibody 14C5 in a non-small cell lung cancer and colon carcinoma model. - Burvenich, I; Schoonooghe, S; Cornelissen, B; Blanckaert, P; Coene, E; Cuvelier, C; Mertens, N; Slegers, G (2005)
PURPOSE: The monoclonal antibody (mAb) 14C5 is a murine IgG1 directed against a yet undefined molecule involved in cell substrate adhesion found on the surface of malignant breast cancer tissue. mAb 14C5 is able to inhibit cell substrate adhesion and invasion of breast cancer cells in vitro. In normal tissues as well as in the stroma surrounding in situ carcinomas of the breast, no expression of the antigen 14C5 occurs. The aim of this study was to investigate the in vitro and in vivo targeting properties of 123I- and 131I-labeled mAb 14C5 as a novel agent for radioimmunodetection and radioimmunotherapy. EXPERIMENTAL DESIGN: Internalization of mAb 14C5 was investigated with 125I-labeled mAb 14C5 and by confocal laser scanning microscopy. Biodistribution studies of 131I-labeled mAb 14C5 and planar gamma imaging were done in nude mice bearing an A549 (non-small cell lung carcinoma) or a LoVo (colon carcinoma) tumor. RESULTS: Internalization studies with both A549 and LoVo cells showed that 125I-labeled mAb 14C5 is slowly internalized with approximately 30% of the initially bound mAb 14C5 internalized after 2 hours at 37 degrees C. Internalization of mAb 14C5 could be visualized with confocal laser scanning microscopy. In vivo, radioisotope uptake peaked at 24 hours for both tumor models (n = 5) with no significant difference in percentage of injected dose/g tissue (A549 10.4 +/- 0.8 and LoVo 9.3 +/- 0.8). Via planar gamma camera imaging, A549 lung tumors as well as LoVo colon tumors could be clearly visualized. CONCLUSIONS: The in vitro and in vivo targeting properties of 123I- and 131I-labeled mAb 14C5 are promising and could provide a new antibody-based agent for radioimmunodetection and radioimmunotherapy of patients bearing antigen 14C5-expressing tumors.